Centering in pottery, poetry, and the person - Richards, Mary Caroline (Middletown, Conn. : Wesleyan University Press, 1989)
A flowing collection of poetry that is also a guide for life.
Cover; Half title; Title; Copyright; Foreword to the Second Edition; Introduction to the Second Edition; Contents; A Foreword: The Arithmetic, the Bush, and the Plan; I. Centering as Dialogue; II. Centering as Transformation; III. Poetry; IV. Pedagogy; V. Ordeal by Fire: Evolution of Person; VI. Recovery of the Child in Manhood; About the Author
Spine title: Centering.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Self-realization.; Spirituality; Réalisation de soi; Spiritualité.; SELF-HELP -- Motivational & Inspirational; SELF-HELP -- Neuro-Linguistic Programming (NLP); SELF-HELP -- Inner Child; SELF-HELP -- Personal Growth -- General; SELF-HELP -- Affirmations; SELF-HELP -- Personal Growth -- Self-Esteem.; Self-realization; Spirituality; Keramik; Kultur; Selbstverwirklichung